1983
DOI: 10.1128/aac.23.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in fever and symptoms in young adults with influenza A/Brazil/78 H1N1 infection after treatment with aspirin or amantadine

Abstract: During an outbreak of influenza A/Brazil/78 H1N1 infection, 47 volunteers with clinical and virological influenza of less than 2 days duration were treated in a randomized double-blind fashion for 5 days with 100 or 200 mg of amantadine daily or with 3.25 g of aspirin daily. The aspirin treatment group defervesced more rapidly (10.3 h versus 21.5 h and 23.6 h; P less than 0.01), but by the second daily follow-up visit, both groups of amantadine recipients exhibited greater symptomatic improvement. Bothersome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 15 publications
(6 reference statements)
3
38
0
1
Order By: Relevance
“…Although our study did not compare 100-and 200-mg doses, the level of efficacy (78%) that we found with the 100-mg regimen was comparable to the efficacy (70 to 90%) reported for 200 mg of amantadine in previous experimental-and natural-challenge studies in adults (5,10,11). One study by Younkin et al (21) demonstrated that 100 mg of amantadine had therapeutic efficacy equal to that of 200 mg. Other studies (16)(17)(18)(19) that have assessed the prophylactic effectiveness of 100 mg of amantadine have been difficult to interpret. Smorondintsev et al (18) in the Soviet Union reported that, compared with placebo, 100 mg of amatitadine significantly reduced serologically confirmed cases of influenza illness during an outbreak; however, they excluded 20% of the participants from the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our study did not compare 100-and 200-mg doses, the level of efficacy (78%) that we found with the 100-mg regimen was comparable to the efficacy (70 to 90%) reported for 200 mg of amantadine in previous experimental-and natural-challenge studies in adults (5,10,11). One study by Younkin et al (21) demonstrated that 100 mg of amantadine had therapeutic efficacy equal to that of 200 mg. Other studies (16)(17)(18)(19) that have assessed the prophylactic effectiveness of 100 mg of amantadine have been difficult to interpret. Smorondintsev et al (18) in the Soviet Union reported that, compared with placebo, 100 mg of amatitadine significantly reduced serologically confirmed cases of influenza illness during an outbreak; however, they excluded 20% of the participants from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Influenza is a major cause of morbidity and mortality despite the availability of effective vaccines and the antiviral drug amantadine hydrochloride (4). Controlled trials have shown that a 200-mg daily dose of amantadine is effective for prophylaxis against and treatment of illness caused by influenza A virus, yet the drug is underused for influenza prevention (5,10,11,(19)(20)(21). This is caused, in part, by concern about drug toxicity; central-nervous-system symptoms occur in approximately 5 to 10% of recipients (4,7,8).…”
Section: Resultsmentioning
confidence: 99%
“…Amantadine and its derivative rimantadine have proven to be effective drugs in humans (and mice) for the prevention of influenza, and the drugs are therapeutic for a more rapid resolution of clinical signs and symptoms (3,10,17,39,49,62,69,70). Rimantadine (Flumadine; Forest Pharmaceuticals, Inc.) is licensed by the U.S. Food and Drug Administration for prophylaxis in adults and children and for treatment in adults.…”
mentioning
confidence: 99%
“…Amantadine also appears superior to aspirin in this regard. In one comparative study, patients taking 3.25 g of aspirin daily became afebrile sooner but had more side effects (insomnia, nausea, ringing in the ears) than amantadine recipients, who experienced an earlier reduction in symptoms and fewer adverse reactions (528). The peripheral pulmonary airway dysfunction accompanying influenza is also improved by amantadine (279), and this may be important for earlier resolution in normal hosts and for minimizing disease in those with underlying pulmonary or cardiac conditions.…”
Section: Antiviral Agents Amantadine and Rimantadinementioning
confidence: 97%